Impact of New Energy Vehicles on Traditional Automotive Manufacturers: The Case of BMW - Liu Chang (SHS Web of Conferences)
This study examines the impact of the rapid development of new energy vehicles on traditional automakers, especially luxury brands such as BMW. As the market for NEVs is expanding rapidly due to increased global environmental awareness and government policy support, traditional automakers are facing fierce competition from emerging electric vehicle companies such as Tesla. BMW has responded positively to the market changes by investing in electrification technologies, launching a series of electric models, and building dedicated production facilities. However, despite the progress BMW has made in the field of new energy vehicles, it still needs to face the challenge of the cost structure of electric vehicles, especially the cost of batteries, which takes up a large proportion of the cost of the entire vehicle. In addition, BMW needs to continuously adjust its pricing strategy and brand positioning to remain competitive in a market that increasingly values environmental protection and technological innovation.